2013
DOI: 10.1002/biof.1089
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial‐dependent anticancer activity of δ‐tocotrienol and its synthetic derivatives in HER‐2/neu overexpressing breast adenocarcinoma cells

Abstract: Anticancer activity and mitochondrial mechanism of the vitamin E form δ-tocotrienol (δ-T3) was investigated in HER-2/neu-overexpressing human SKBR3 and murine TUBO breast cancer cells. δ-T3 was confirmed to possess high cytotoxic and apoptotic activity in SKBR3 cells as compared with all natural forms of vitamin E and several synthetic forms that included novel derivatives with the same backbone of δ-T3 such as δ-tocotrienyl-succinyl amide (δ-T3AS) and the redox-active analogue δ-tocotrienyl amine (δ-T3NH2). A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 38 publications
1
21
0
Order By: Relevance
“…The observation that δ-TT is associated with a significant proapoptotic effect in melanoma cells is in agreement with the reported antitumor activity of TTs (mainly δ-TT and γ-TT) in different types of tumors19333544.…”
Section: Discussionsupporting
confidence: 91%
“…The observation that δ-TT is associated with a significant proapoptotic effect in melanoma cells is in agreement with the reported antitumor activity of TTs (mainly δ-TT and γ-TT) in different types of tumors19333544.…”
Section: Discussionsupporting
confidence: 91%
“…These same studies also confirmed that tocotrienol‐induced apoptosis was mediated independently of caspase 9 signaling . These results appeared to suggest that tocotrienol‐induced apoptosis was mediated by the extrinsic, but not the intrinsic apoptotic pathway in the highly malignant mouse +SA mammary tumor cell line , but is involved in human breast cancer cell lines . However, as +SA cells were found to contain nonfunctional death receptors, the exact mechanism involved in mediating the apoptotic effects of tocotrienol in these cells remained unclear .…”
Section: Apoptotic Effects Of Tocotrienolmentioning
confidence: 63%
“…The same type of considerations have been made on the quinone analogues of VOO phenolics . The mitochondrial‐dependent pro‐apoptotic activity of α‐T3 in HER2‐neu positive breast cancer cells and the corresponding in vivo anticancer activity are an example of these properties . Molecular players in this signaling of vitamin E‐related molecules include among the others, phospholipase A2, PKC isoforms and their corresponding phosphatases, pro‐survival and stress‐related MAPKs, and key regulatory components of cell cycle (reviewed in ).…”
Section: Signaling and Gene Response Of Vitamin E: A Focus On The Maimentioning
confidence: 99%